Molecular solubilization of fullerene C60 in water by γ-cyclodextrin thioethers - Wang, Hai Ming; Wenz, Gerhard (Beilstein Journal of Organic Chemistry, 2012)
Various hydrophilic γ-cyclodextrin (CD) thioethers, containing neutral or ionic side arms were found to form molecular disperse solutions of C60 in water reaching concentrations of 15 mg/L. Equilibrium state was approached after seven days without the use of organic cosolvents. The 1:2 stoichiometry of the C60/γ-CD thioether complexes was demonstrated by a parabolic phase-solubility diagram. In contrast, native γ-CD forms nanoparticles with C60. Particle sizes of C60 were determined by dynamic light scattering.
Keywords: C60; cyclodextrins; dynamic light scattering; particle size; solubilization; UV spectrum

(untitled) - Kroto, H. W.; Heath, J. R.; O'Brien, S. C.; Curl, R. F.; Smalley, R. E. (Nature, 1985)

(untitled) - Krätschmer, W.; Lamb, L. D.; Fostiropoulos, K.; Huffman, D. R. (Nature, 1990)

(untitled) - Nakamura, E.; Isobe, H. (Acc. Chem. Res., 2003)

(untitled) - Da Ros, T.; Prato, M. (Chem. Commun., 1999)

(untitled) - Jensen, A. W.; Wilson, S. R.; Schuster, D. I. (Bioorg. Med. Chem., 1996)

(untitled) - Hirsch, T.; Kettenberger, H.; Wolfbeis, O. S.; Mirsky, V. M. (Chem. Commun., 2003)

(untitled) - Hebard, A. F.; Rosseinsky, M. J.; Haddon, R. C.; Murphy, D. W.; Glarum, S. H.; Palstra, T. T. M.; Ramirez, A. P.; Kortan, A. R. (Nature, 1991)

(untitled) - Dai, L. M. (Polym. Adv. Technol., 1999)

(untitled) - Halls, J. J. M.; Pichler, K.; Friend, R. H.; Moratti, S. C.; Holmes, A. B. (Appl. Phys. Lett., 1996)

(untitled) - Semenov, K. N.; Charykov, N. A.; Keskinov, V. A.; Piartman, A. K.; Blokhin, A. A.; Kopyrin, A. A. (J. Chem. Eng. Data, 2010)

(untitled) - Heymann, D. (Fullerene Sci. Technol., 1996)

(untitled) - Sijbesma, R.; Srdanov, G.; Wudl, F.; Castoro, J. A.; Wilkins, C.; Friedman, S. H.; DeCamp, D. L.; Kenyon, G. L. (J. Am. Chem. Soc., 1993)

(untitled) - Lyon, D. Y.; Adams, L. K.; Falkner, J. C.; Alvarez, P. J. J. (Environ. Sci. Technol., 2006)

(untitled) - Fortner, J. D.; Lyon, D. Y.; Sayes, C. M.; Boyd, A. M.; Falkner, J. C.; Hotze, E. M.; Alemany, L. B.; Tao, Y. J.; Guo, W.; Ausman, K. D.; Colvin, V. L.; Hughes, J. B. (Environ. Sci. Technol., 2005)

(untitled) - Hirsch, A.; Lamparth, I.; Karfunkel, H. R. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Deguchi, S.; Alargova, R. G.; Tsujii, K. (Langmuir, 2001)

(untitled) - Scrivens, W. A.; Tour, J. M.; Creek, K. E.; Pirisi, L. (J. Am. Chem. Soc., 1994)

(untitled) - Torres, V. M.; Posa, M.; Srdjenovic, B.; Simplício, A. L. (Colloids Surf., B, 2011)

(untitled) - Haino, T.; Yanase, M.; Fukunaga, C.; Fukazawa, Y. (Tetrahedron, 2006)

(untitled) - Ikeda, A.; Suzuki, Y.; Yoshimura, M.; Shinkai, S. (Tetrahedron, 1998)

(untitled) - Andersson, T.; Nilsson, K.; Sundahl, M.; Westman, G.; Wennerström, O. (J. Chem. Soc., Chem. Commun., 1992)

(untitled) - Yoshida, Z.-i.; Takekuma, H.; Takekuma, S.-i.; Matsubara, Y. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Wenz, G. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Wenz, G. (Adv. Polym. Sci., 2009)

Cyclodextrins and their Complexes: Chemistry, Analytical Methods, Applications - Dodziuk, H. (Wiley-VCH, 2006)

(untitled) - Rekharsky, M. V.; Inoue, Y. (Chem. Rev., 1998)

(untitled) - Liu, L.; Guo, Q.-X. (J. Inclusion Phenom. Macrocyclic Chem., 2002)

(untitled) - Müller, A.; Wenz, G. (Chem.–Eur. J., 2007)

(untitled) - Raffaini, G.; Ganazzoli, F. (J. Phys. Chem. B, 2010)

(untitled) - Priyadarsini, K. I.; Mohan, H.; Tyagi, A. K.; Mittal, J. P. (J. Phys. Chem., 1994)

(untitled) - Komatsu, K.; Fujiwara, K.; Murata, Y.; Braun, T. (J. Chem. Soc., Perkin Trans. 1, 1999)

(untitled) - Konstantaki, M.; Koudoumas, E.; Couris, S.; Janot, J. M.; Eddaoudi, H.; Deratani, A.; Seta, P.; Leach, S. (Chem. Phys. Lett., 2000)

(untitled) - Wenz, G.; Strassnig, C.; Thiele, C.; Engelke, A.; Morgenstern, B.; Hegetschweiler, K. (Chem.–Eur. J., 2008)

(untitled) - Steffen, A.; Thiele, C.; Tietze, S.; Strassnig, C.; Kämper, A.; Lengauer, T.; Wenz, G.; Apostolakis, J. (Chem.–Eur. J., 2007)

(untitled) - Wang, H. M.; Soica, C. M.; Wenz, G. (Nat. Prod. Commun., 2012)

(untitled) - Bensasson, R. V.; Bienvenue, E.; Dellinger, M.; Leach, S.; Seta, P. (J. Phys. Chem., 1994)

(untitled) - Kuroda, Y.; Nozawa, H.; Ogoshi, H. (Chem. Lett., 1995)

(untitled) - Wang, H. M.; Wenz, G. (Chem.–Asian J., 2011)

(untitled) - Geckeler, K. E.; Hirsch, A. (J. Am. Chem. Soc., 1993)

(untitled) - Higuchi, T.; Connors, K. (Adv. Anal. Chem. Instrum., 1965)

(untitled) - Singh, R.; Tonnesen, H. H.; Vogensen, S. B.; Loftsson, T.; Másson, M. (J. Inclusion Phenom. Macrocyclic Chem., 2010)

(untitled) - Murthy, C. N.; Geckeler, K. E. (Chem. Commun., 2001)

(untitled) - Hou, W.-C.; Jafvert, C. T. (Environ. Sci. Technol., 2009)

(untitled) - Jansook, P.; Moya-Ortega, M. D.; Loftsson, T. (J. Inclusion Phenom. Macrocyclic Chem., 2010)

(untitled) - Puskás, I.; Schrott, M.; Malanga, M.; Szente, L. (J. Inclusion Phenom. Macrocyclic Chem., 2012)

(untitled) - Ruf, H.; Georgalis, Y.; Grell, E. (Methods Enzymol., 1989)

(untitled) - Alexander, M.; Dalgleish, D. G. (Food Biophys., 2006)

(untitled) - Burchard, W. (Adv. Polym. Sci., 1983)

(untitled) - Mie, G. (Ann. Phys., 1908)